Influence of temperature on regulation of key virulence and stress response genes in Listeria monocytogenes biofilms. (May 2023) - Poimenidou, Sofia V.; Caccia, Nelly; Paramithiotis, Spiros; Hébraud, Michel; Nychas, George-John; Skandamis, Panagiotis N.
Abstract: Temperature is a major determinant of Listeria (L.) monocytogenes adherence and biofilm formation on abiotic surfaces. However, its role on gene regulation of L. monocytogenes mature biofilms has not been investigated. In the present study, we aimed to evaluate the impact of temperature up- and down-shift on L. monocytogenes biofilms gene transcription. L. monocytogenes strain EGD-e biofilms were first developed on stainless steel surfaces in Brain Heart Infusion broth at 20 °C for 48 h. Then, nutrient broth was renewed, and mature biofilms were exposed to 10 °C, 20 °C or 37 °C for 24 h. Biofilm cells were harvested and RNA levels of plcA, prfA, hly, mpl, plcB, sigB, bapL, fbpA, fbpB, lmo2178, lmo0880, lmo0160, lmo1115, lmo 2089, lmo2576, lmo0159 and lmo0627 were evaluated by quantitative RT-PCR. The results revealed an over-expression of all genes tested in biofilm cells compared to planktonic cells. When biofilms were further allowed to proliferate at 20 °C for 24 h, the transcription levels of key virulence, stress response and putative binding proteins genes plcA, sigB, fbpA, fbpB, lmo1115, lmo0880 and lmo2089 decreased. A temperature-dependent transcription for sigB, plcA, hly, and lmo2089 genes was observed after biofilm proliferation at 10 °C or 37 °C. Our findings suggest that temperature differentially affects gene regulation of L. monocytogenes mature biofilms, thus modulating attributes such as virulence, stress response and pathogenesis. Highlights: All tested genes were upregulated in L. monocytogenes biofilms compared to planktonic cells. Transcription of key virulence and stress response genes in mature biofilms was modulated in a temperature-dependent manner. Mature biofilms further exposed to 20 °C for 24 h exhibited decreased transcript levels of sigB, plcA, fbpA and fbpB genes.